Characteristics of CoVID-19 in children: the first experience in the hospital of st. Petersburg - E. A. Dondurey; L. N. Isankina; O. I. Afanasyeva; A. V. Titeva; T. V. Vishnevskaya; V. A. Kondrat`ev; I. A. Gryaznova; M. V. Berezina; M. A. Zolotova; V. M. Volzhanin (Журнал инфектологии)
Objective: to identify the clinical, laboratory and epidemiological features of the new coronavirus (CV) infection in the provision of specialized medical care to children in the megalopolis of the Russian Federation. Methods: 674 cases of hospitalization of patients from birth to 17 years old inclusive with confirmed COVID-19 in the period from March 26 to June 26, 2020 in a children’s multidisciplinary hospital in St. Petersburg. Diagnostics of SARS-COV-2 in upper respiratory tract (URT) smears was carried out by PCR (a set of reagents for detecting RNA of coronavirus 2019-nCoV by PCR with hybridization-fluorescence detection “Vector-PCRRV-2019-nCoV-RG”). Patients underwent 4 (3; 5) repeated examinations depending on the diagnosis of the referral, as well as the duration of the convalescent virus carriage. The analysis of the severity of the course of the disease, the main clinical manifestations and their relationship with the development of pneumonia, as well as the epidemiological features of COVID-19 in children. The duration of inpatient treatment, outcomes and the need for intensive care are described. Changes in a number of laboratory parameters on analyzers made in the USA were assessed: a clinical blood test on a hematological one - Coulter UniCel (Beckman Coulter), a biochemical blood test on a biochemical one - Uni Cel DxC (Beckman Coulter), a coagulogram on a hemostasis analyzer (Instrumentation Laboratory). Results: Overall, there was a favorable course of COVID-19 in children. Intensive therapy was required only in 3.6% of cases with a total mortality rate of 0.15%, Kawasakilike syndrome was recorded in 0.3% of cases. In 1/3 of patients, prolonged viral shedding from the upper respiratory tract was detected. In children, intrafamilial infection from adults was in the lead; schoolchildren accounted for half of all hospitalizations. A distinctive feature of the new infection was mild clinical symptoms with fever and catarrhal symptoms up to 4/5 of cases, gastrointestinal symptoms - in every third patient. There were no significant differences in the severity of the disease by age. Pneumonia, diagnosed in ¾ cases by computed tomography, complicated the course in 13.1% of cases. The defeat of the lungs was accompanied by fever and dry cough, and in a more severe course: desaturation, chest pains, a feeling of insufficiency of inspiration. The age peaks of the incidence of pneumonia were revealed: at 4, 9, 12 years old and at the age of 17 years, the maximum (in 1/3 of cases). Laboratory changes were insignificant and quickly reversible. Conclusion: the course of COVID-19 in children in the megalopolis of Russia is comparable with foreign information. However, taking into account the experience of “Spanish ‘flu”, it is possible that in pediatric practice the number of severe forms and unfavorable outcomes may change in the near future, especially due to the difficulty of diagnosing Kawasaki-like syndrome and the need for a multidisciplinary approach to the treatment of such patients. Currently, the most vulnerable to the new CV are children with severe oncological, neurological and cardiovascular pathology, who have a rapid decompensation of the underlying disease against the background of COVID-19.